Solve for x square root of x=0.6

Math
x=0.6
To remove the radical on the left side of the equation, square both sides of the equation.
x2=0.62
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in (x12)2.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
x12⋅2=0.62
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
x12⋅2=0.62
Rewrite the expression.
x1=0.62
x1=0.62
x1=0.62
Simplify.
x=0.62
Raise 0.6 to the power of 2.
x=0.36
x=0.36
Solve for x square root of x=0.6

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top